2009
DOI: 10.4161/derm.1.3.9638
|View full text |Cite
|
Sign up to set email alerts
|

Acne and smoking

Abstract: BACKGROUND.: Post-adolescent acne is an inflammatory disorder, whose cause is unknown. Contrasting data are available on correlation between acne and smoking habit. OBJECTIVES.: To verify the frequency of clinically non-inflammatory (atypical) post-adolescent acne (APAA) among women, a possible correlation with cigarette smoking, possible differences in sebum composition in a group of female smokers with acne compared to healthy smokers and non-smokers. METHOD AND RESULTS.: 1046 randomly selected women (25-50-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
2
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 34 publications
5
52
2
10
Order By: Relevance
“…En effet, Peiqi Su [15], a rapporté que 18.9 % des sujets croient que l'acné a un lien avec la consommation de tabac. Capitanio [20] a positivement corrélée l'acné au tabagisme par le nombre de cigarettes quotidiennement fumés et la prévalence de l'acné d'apparition tardive. T. Chuh et col [21], dans une étude réalisée à Hong Kong et en Inde, l'association du tabagisme à l'acné chez les hommes a rapporté une augmentation de la sévérité de l'acné significativement associée à une augmentation du stress.…”
Section: Resultsunclassified
“…En effet, Peiqi Su [15], a rapporté que 18.9 % des sujets croient que l'acné a un lien avec la consommation de tabac. Capitanio [20] a positivement corrélée l'acné au tabagisme par le nombre de cigarettes quotidiennement fumés et la prévalence de l'acné d'apparition tardive. T. Chuh et col [21], dans une étude réalisée à Hong Kong et en Inde, l'association du tabagisme à l'acné chez les hommes a rapporté une augmentation de la sévérité de l'acné significativement associée à une augmentation du stress.…”
Section: Resultsunclassified
“…The skin functions as an immune organ against outside chemicals and pathogens. Studies on epidemiology between smoking and skin disease have revealed that cigarette smoking is closely related to inflammatory skin disease and pilosebaceous unit-related diseases such as acne and acne inversa (hidradenitis suppurativa) (Ortiz and Grando, 2012;Capitanio et al, 2009;Bergler-Czop et al, 2015). However, little is known about the metabolism and biology of inflammatory reactions to cigarette smoke in the skin, especially in the pilosebaceous units.…”
Section: Introductionmentioning
confidence: 98%
“…[28][29][30] Meanwhile, some studies fail to show or reveal a protective effect of smoking: a recent study found tobacco-smoking was protective against acne, but confirmed an association between cannabis-smoking and acne in both adolescent and young adults. 17 An older study claims that nicotine possibly plays an anti-inflammatory action on acne, being protective against it.…”
Section: 26mentioning
confidence: 99%